2005
DOI: 10.1016/j.preteyeres.2005.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic transmission at retinal ribbon synapses

Abstract: The molecular organization of ribbon synapses in photoreceptors and ON bipolar cells is reviewed in relation to the process of neurotransmitter release. The interactions between ribbon synapseassociated proteins, synaptic vesicle fusion machinery and the voltage-gated calcium channels that gate transmitter release at ribbon synapses are discussed in relation to the process of synaptic vesicle exocytosis. We describe structural and mechanistic specializations that permit the ON bipolar cell to release transmitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
231
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 209 publications
(250 citation statements)
references
References 359 publications
(576 reference statements)
10
231
1
Order By: Relevance
“…5B). The integral of the deconvolved average AF response with 5 mM EGTA was best fit with two rather than three exponentials: 1 ϭ 27 ms, 2 (Fig. 5C, red trace).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…5B). The integral of the deconvolved average AF response with 5 mM EGTA was best fit with two rather than three exponentials: 1 ϭ 27 ms, 2 (Fig. 5C, red trace).…”
Section: Resultsmentioning
confidence: 98%
“…Synaptic ribbons, presynaptic structures presenting a halo of tethered vesicles, also found in retinal photoreceptors and bipolar cells (2), are thought to facilitate accumulation of vesicles presynaptically (3). Postsynaptically, ␣-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptors mediate fast synaptic transmission (4).…”
mentioning
confidence: 99%
“…e d u Abbreviations used in this paper: BC, bipolar cell; CaM, calmodulin; EPSC, excitatory postsynaptic current; ERG, electroretinogram; HC, horizontal cell; IRP, immediately releasable pool; MLCK, myosin light chain kinase; PPR, paired pulse ratio; RBC, rod BC; TIRFM, total internal reflection fluorescence microscopy. primed vesicles for release at the presynaptic membrane (Heidelberger et al, 2005;Snellman et al, 2011). Recent studies have shown that the interplay of vesicle release and replenishment at the ribbon are important in encoding luminance and contrast by cones (Jackman et al, 2009;Babai et al, 2010) and rod BCs (RBCs; Oesch and Diamond, 2011;Ke et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Photoreceptors have an unusual type of synapse in their terminals, the ribbon synapse, which is structurally and functionally specialized for a large and tonic release of neurotransmitter (6)(7)(8)(9)(10). The synaptic ribbon is a plate-like structure that extends from the site of transmitter release into the synaptic terminal cytoplasm and has hundreds of synaptic vesicles tethered to it (11).…”
mentioning
confidence: 99%